2003
DOI: 10.1210/jc.2001-011813
|View full text |Cite
|
Sign up to set email alerts
|

Management of Occult Adrenocorticotropin-Secreting Bronchial Carcinoids: Limits of Endocrine Testing and Imaging Techniques

Abstract: The differential diagnosis and the identification of the source of ACTH in occult ectopic Cushing's syndrome due to a bronchial carcinoid still represents a challenge for the endocrinologist. We report our experience in six patients with occult bronchial carcinoid in whom extensive hormonal, imaging, and scintigraphic evaluation was performed. All patients presented with hypercortisolism associated with high plasma ACTH values. The CRH test and high dose dexamethasone suppression test suggested an ectopic sour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0
8

Year Published

2005
2005
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 38 publications
0
22
0
8
Order By: Relevance
“…It has been suggested that no single endocrine test and/or imaging procedure are accurate enough to diagnose and localise ectopic ACTH/CRH-producing bronchial carcinoids, particularly as false positive IPSS results may occasionally be obtained, albeit very rarely (Young et al 1998, de Herder & Lamberts 1999, Baudin et al 2001, Loli et al 2003. In such cases, scintigraphy with 111 In-octreotide, particularly after correction of hypercortisolaemia, and PET using several novel tracers can be used to reveal confounding cases eluding localisation (de Herder et al 1994, Tsagarakis et al 2003, Kaltsas et al 2004b, Markou et al 2005.…”
Section: Humoral Pnss In Net Cushing's Syndromementioning
confidence: 99%
“…It has been suggested that no single endocrine test and/or imaging procedure are accurate enough to diagnose and localise ectopic ACTH/CRH-producing bronchial carcinoids, particularly as false positive IPSS results may occasionally be obtained, albeit very rarely (Young et al 1998, de Herder & Lamberts 1999, Baudin et al 2001, Loli et al 2003. In such cases, scintigraphy with 111 In-octreotide, particularly after correction of hypercortisolaemia, and PET using several novel tracers can be used to reveal confounding cases eluding localisation (de Herder et al 1994, Tsagarakis et al 2003, Kaltsas et al 2004b, Markou et al 2005.…”
Section: Humoral Pnss In Net Cushing's Syndromementioning
confidence: 99%
“…It may be particularly useful in the detection of lesions not visualized by CT or MRI, particularly occult bronchial carcinoids (74). However, in most studies, all tumors disclosed by SRS were apparent on conventional imaging (2,4,44).…”
Section: Somatostatin Receptor Scintigraphy (Srs)mentioning
confidence: 99%
“…However, in most studies, all tumors disclosed by SRS were apparent on conventional imaging (2,4,44). An analysis of 7 studies examining the usefulness of SRS in EAS demonstrated diagnostic sensitivity ranging from 33% to 80% for tumor localization (44,71,(74)(75)(76)(77)(78)(79).…”
Section: Somatostatin Receptor Scintigraphy (Srs)mentioning
confidence: 99%
See 2 more Smart Citations